Individual Contributions of Adsorbed and Free Chains to Microscopic Dynamics of Unentangled poly(ethylene Glycol)/Silica Nanocomposite Melts and the Important Role of End Groups: Theory and Simulation - Skountzos, Emmanuel N.; Tsalikis, Dimitrios G.; Stephanou, Pavlos S.; Mavrantzas, Vlasis G. (My University, 2021)
Molecular dynamics simulations and Rouse theory suitably adapted for polymer chains adsorbed by one or both of their ends are combined to offer a quantitative description of the local structure and microscopic dynamics in attractive polymer nanocomposite melts using a poly(ethylene glycol) (PEG)/silica nanocomposite as a model system. Our work reveals that the adsorbed layer around the silica nanoparticle is far from being characterized as "glassy"or "immobilized"since adsorbed polymer segments in the form of tails and loops on silica exhibit appreciable mobility locally, which helps adsorbed chains to relax at short length scales, albeit rather slowly. The simulations also reveal significant differences in the structural and dynamic properties of the PEG/silica nanocomposite melts studied for different terminal groups (hydroxyl versus methoxy) of the PEG chains, originating from the different ways that polymer chains adsorb on the silica surface: hydroxyl-terminated PEG chains are adsorbed by their ends giving rise to a brush-like structure, whereas methoxy-terminated ones are adsorbed equally probably along their entire contour, thus resulting in better packing of adsorbed segments. Due to the dense interfacial layer that develops in both cases, the diffusive behavior of free chains is also affected (it slows down compared to that in the corresponding pure PEG melt), especially in the nanocomposite where PEG chains are terminated with hydroxyl groups. Direct comparison of simulation and theoretical predictions with previously reported experimental data in the literature for the dynamic structure factor [Glomann et al., Phys. Rev. Lett. 2013, 110, 178001] for the same systems under the same temperature and pressure conditions reveals excellent agreement.
Keywords: Polymer molecular weight; PEG matrix; Neutron Spin Eco; Early molecular dynamics